PELATIHAN LITERASI DIGITAL BAGI PEMILIH PEMULA SMA GENIUS TANGERANG MENJELANG PEMILU 2024 - Pamungkas, Sigit; Rondonuwu, Roy; G. Poluan, Pincanny (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Digital literacy for first-time voters has been widely introduced in high schools. One such initiative was carried out for the students of GENius High School in Tangerang. The faculty members from the Communication Science Program at FISIP UPH conducted a Community Service Program (PkM) for GENius High School students in March 2023. The goal was to provide a basic understanding of the 2024 election and identify the participants' information needs. One of the findings from the questionnaire distributed to the entire population was that participants needed information on how to assess the quality of election candidates they will vote for. The results of this questionnaire will be used as a reference for digital literacy materials in the form of modules and videos. Keywords: 2024 Election, Digital Literacy, First-time Voters